PENGARUH PUSH-PULL-MOORING FACTOR TERHADAP SWITCHING BEHAVIOR MELALUI SWITCHING INTENTION DARI ANDROID KE IOS - Ashari, Ismahmudi Harits; Suryati, Suryati (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2025)
The widespread use of smartphones has increased competition between companies, so understanding consumer switching behavior is very important, especially in the archipelago. The purpose of this study was to examine the factors influencing the behavior of Generation Z from Android to iOS in Solo Raya, Indonesia, using the Push-Pull-Mooring (PPM) framework. An online survey of 226 respondents and processed data using a quantitative method analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results revealed that the Push factor (low satisfaction, privacy concerns, obsolete features) and Pull factors (alternative appeal, perceived usability, hedonic motivation) positively and significantly influenced the intention to switch. In contrast, Mooring factors (subjective norms, switching costs, prior experience) had a non-significant negative impact on switching intent. Switching intentions have a positive and significant impact on actual behavior. The study concluded that the thrust and pull factors play an important role in shaping switching intentions, while the mooring factor has a more limited effect. These findings provide valuable insights for smartphone companies, especially Android and iOS, to better understand consumer behavior and develop effective strategies to overcome market competition.